Analisis Kelengkapan Pengisian Ringkasan Pulang Terhadap Kelancaran Klaim Badan Penyelenggaraan Jaminan Sosial Kesehatan di Rumah Sakit PTPN VIII Subang - Aminuddin Sholeh (Indonesian Journal Publisher, 2023)
One of the existing forms of one of the medical records is a discharge..sumaary containing the patient's clinical data. The purpose of this study is to identify the completeness of filling out the discharge summary sheet of the medical record of the patient of the BPJS hospital in the PTPN VIII Subang hospital in 2021. This type of study is a descriptive quantitative study. Randomized Sampling Technique The population of this study is a summary extract from the medical record of patient. The sample in this study is 84 discharge forms of a patient, the results showed the completeness of filling in the patient's identification by date of birth by 95% and by gender equal to 78%. The completeness of completion of the important report for the obsolete element is 79%, and for the input of the diagnostic element - 67%. The completeness of authentication for the item Date of completion is 72%, and for the item